Efisiensi produksi budidaya ikan bandeng (Chanos chanos) di Kecamatan Tinanggea Kabupaten Konawe Selatan - Nining Putriyani; Budiyanto; Yusuf, Sarini; Idris, Muhammad; Ruslaini; Riani, Irdam (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aimed to determine some factors that affect production and efficiency of milkfish culture in Tinanggea District, South Konawe Regency. The experiment was conducted from August to September 2022. The total number of samples was 24 people.  Determination of the sample was performed in simple randomization. Some variables collected were the total number of productions, wide of fish culture area employer, the total number of milkfish juvenile, the total number of fertilizers, and the total number of limes.  Data analyses were couple non-linear regression and analysis of production efficiency. The results showed that utilization together of production factors (area-wide, employer, total number of milkfish juvenile, total number of fertilizer, and total number of lime) were significantly different on milkfish production, whereas in partially or individually of production factors such as employer, total number of fertilizer or total number of limes were also significantly different of milkfish production.  Utilization of all production factors was not efficient.